Production animale et vocation pastorale des terres au Mali et dans les pays saheliens - Swift, J. (CIPEA, 1980)
Note summarizing general data on the place of livestock production and pastoral land use in the economies of Sahelian countries in order to show the extent to which Mali's land resources & the place of livestock in its economy are representative of the Sahelian countries, & to assess the importance of livestock to the economies of 6 Sahelian countries: Senegal, Mauritania, Mali, Niger, Upper Volta & Chad.